Assessment of efficacy and safety of dapsone gel 5% in the treatment of acne vulgaris - Al-Ani, Yasir mansour (AL-Kindy College Medical Journal, 2019)
ABSTRACTBackground : Acne vulgaris is acommon skin disease, affecting more than 85% ofadolescents and often continuing into adulthood.People between 11 and 30 years of age and up to5% of older adults. For most patients acne remainsa nuisance with occasional flares of unsightlycomedones, pustules and nodules. For other lessfortunate persons, the sever inflammatory responseto Propionibacterium acnes (P.acnes) results inpermanentMethods: Disfiguring scars. (1, 2) Stigmata of severacne cane lead to social ostracism, withdrawalfrom society and severe psychologicdepression (1-4).Result Pathogenesis of acne Traditionally, acnehas been thought of as a multifactorial disease ofthe folliculosebaceous unit, involving excesssebum production, abnormal follicularhyperkeratinization, overgrowth ofPropionibacterium acnes, and inflammation (Fig2). Recent laboratory and clinical investigationsinto the roles of the innate immune system andextracellular matrix remodeling proteins have shedadditional light on this pathogenetic process (5-7).Role of androgens: Activity of type 1 5areductaseenzyme was shown to predominate inhuman sebaceous glands and epidermis. Thisenzyme is responsible for the conversion oftestosterone to the more potent androgen,dihydrotestosterone (DHT). DHT in turn is thoughtto mediate androgen dependent skin diseases suchas acne, hirsutism and androgenetic alopecia (13)The enzyme 5a-reductase type 1 has been studiedin those with and without acne and it has beenhypothesized that those with acne might have moreactive 5a-reductase type 1 .(2)Conclusion : The prominent role of hormones inthe pathophysiology of acne has long beenrecognized and corroborated by clinical andexperimental observations and therapeuticexperience (14). Although acne is not considered aprimary endocrine disorder, androgens, such asdihydrotestosterone, dehydroepiandrosteronesulfate, and testosterone, and growth hormone andinsulin-like growth factors, have all beenimplicated in the pathogenesis of acne (15).Corresponding address to :Dr. Yasir Mansour Mohamed Al-AniIslam Mohammad Nabil El Helou